Implementasi SMART LIBRARY menggunakan konsep inernet of thing dalam meningkatkan pelayanan perpustakaan - Al Alim Manurung, Muhammad Khoir (Universitas Islam Negeri Sumatera Utara, 2019)
This paper discusses how the library is transformed and develops along with the development of the times in order to compete with things that rival the library, such as ebooks and books by utilizing other technologies. In educating the life of the nation, especially students as academic people as well as iron stock for the civilization of the nation and state, the existence of a library is a basic thing that must be considered, and of course must be integrated with technological developments to provide ease of service to users and can maximize library services and of course will increase the attractiveness of the library itself. The evolution of library services today has evolved digitally, but with increasingly rapid and instant technological developments so that digitalized library services are still considered to be less effective and less efficient in time and costs. Therefore, the author offers an idea namely Smart library, which is a mobile application-based library information system with the integration of IoT concepts in libraries that can be used by users using their respective smartphones. This paper also contains a system of smart library usage, its ease, obstacles that have been found by the community with the use of manual systems and how to progress when using systems that have been transformed with technology.